Socialization of Home Garden Intensification as a Source of Family Food and Improvement of Family Nutrition in Pasinggangan Village, Banyumas District - setiyaningsih, Lilik; Asro Nurhabib; Irfan Hanifa; Febrian Arya Adi Nugraha; Urfaza Atstsaqafi; Afif Aufan Marsay; Safira Aulia Salsabila; Abdurachman; Atiqah Nur Sa'idah; Yustika Ajeng Meysyaroh; Laely Fika Nurrahma; Nur Mahda Yuda P. A. W; Tika Difa Saftri; Inayatul Maftuchah; Mentari Rahmah Adiyanti (Universitas Mataram, 2025)
The use of home gardens as a source of food and for improving family nutrition is increasingly recognized as a solution for strengthening family food security. This initiative aims to shift the mindset of the community in Pasinggangan Village, Banyumas District, in transforming previously unproductive backyard spaces into sources of fresh food, particularly vegetables, family medicinal plants (TOGA), and fish farming using an aquaponics system (budikdamber). The program involves 35 homemakers who are members of the PKK organization in Pasinggangan Village. The methods used include socialization, interactive discussions, field demonstrations, and the distribution of seeds and chili plant seedlings. The results of the activity show significant changes in the utilization of previously vacant yards into productive land for growing vegetables and medicinal plants, as well as the implementation of the budikdamber system for fish farming. Participants expressed high levels of satisfaction and continued the activities by forming backyard farming groups as a form of program sustainability. This program makes an important contribution to enhancing community awareness, knowledge, and skills regarding sustainable agriculture. However, ongoing guidance and further training are needed to address technical challenges and improve the availability of organic fertilizers in the community. This program is expected to be replicated in other areas with similar characteristics to support national food security.